Negotiation Dynamics between Panglima Laot’s Authority and Islamic Law in Aceh’s Coastal Communities - bin Muhammaddiah, Muhammad Rusdi; Riza, Muhammad; Umami, Yusra; Muhazir, Muhazir; Fajar, Nurul Izdihar (Program Studi Hukum Keluarga Islam, 2026)
This study examines the complex dynamics between Panglima Laot's traditional authority as eleume (sorcery) holders and Islamic law implementation in Aceh's coastal communities, identifying effective harmonization strategies. The research addresses a critical gap in understanding how traditional maritime institutions negotiate their roles amid growing demands from Islamic law, particularly regarding the transformation of eleume practices and ritual adaptations. Previous studies have focused primarily on formal Sharia aspects without examining traditional ritual dynamics, leaving crucial aspects of cultural negotiation unexamined. Using a qualitative approach with ethnographic methods and case studies in Langsa City and East Aceh District, the study involved Panglima Laot, religious leaders, traditional leaders, and fishing communities as informants, using participatory observation, semi-structured in-depth interviews, and document analysis. Results revealed Panglima Laot's significant transformation through the integration of Islamic monotheism and fiqh values into traditional maritime rituals, replacing mantras with Quranic and Hadith prayers. Successful harmonization was achieved through intensive dialogue and local wisdom-based institutional strengthening, with customary institutions mediating between formal authorities and traditional fishing communities. These findings contribute to Islamic law anthropology studies and provide a conceptual framework for harmonizing tradition and modernity in other Indonesian coastal areas.